The motion of an ion in a synthetic molecular ion channel - Morton-Blake, Tony (My University, 2013)
A molecular dynamics investigation is conducted on the passive transport of Na+ ions through a synthetic channel in aqueous NaCl medium, the channel consisting of fourteen 15-crown-5 rings rigidly linked in a stacked configuration. The investigation studies the entry and exit of Na+ ions by applied electric fields; the Cl? ions are not admitted because of the channel?s unfavourable axial electrostatic potential for anions, and the water molecules are too large to enter. The Na+ ions exhibit damped oscillatory dynamics, for which frequencies and damping parameters are calculated, and possible applications of the system are discussed.
PUBLISHED
Keywords: Molecular dynamics; Ion migration; Electric fields; Oscillating trajectories; Infrared radiation; Nanoscience & Materials